Elaboración de bocashi utilizando microorganismos en diferentes dosis, preparado con estiércol y residuos vegetales en el Cantón Quevedo. - Albarracín Macías, kleber Raúl (2019)
Annually, the ignorance of the farmers due to the misuse of chemical inputs and the improper handling of agricultural residues become a potential for environmental pollution; with the appearance of new diseases that affect human and animal health. The objective was to prepare Bocashi with manure and plant residues in the Quevedo canton by applying microorganisms in different doses. Two factors were studied, being factor A: three types of microorganisms, which one of them was acquired from the Association of Graduates EARTH-ECUADOR, commercially known as EM • 1® in the production of local microorganisms, two types of capture were made ; Factor B: three different doses which consisted of the low dose (0.12 L / m3), medium (0.25 L / m3), and high (0.50 L / m3), to get the low dosage, Medium and high was split with the local and commercial dose found at 0.25 L / m3, with a 5% solution of the microorganisms. It was possible to determine by means of the test of captures of microorganisms, that the best site of origin is the guadua cane crops with the position of the captor facing up, obtaining a greater amount of beneficial microorganisms such as Trichodermas spp, Saccharomyces spp; in the dilution of 1gr of sample in 100 ml of water, recovering 370 μl of the stock solution, bacteria such as Lactobacillus spp and Pseudomona spp. It was determined that the highest content of nitrogen, potassium and calcium with 0.70%, 0.55%, 0.97%; as well as, the best characteristics for a good quality fertilizer with a pH of 7.0, carbon / nitrogen ratio with 12.88% and presenting the highest weight ratio with 32.73 kg, were presented by the treatment of microorganisms of Capture one with doses of 0.50 L/m3. The highest concentration of micro elements such as zinc with 66.0 ppm and iron with 842 ppm was presented by commercial treatment with doses of 0.50 L/m3 and the highest boron content with 25 ppm and copper with 38 ppm was the application of Commercial microorganism with a dose of 0.25 L/m3. Production costs in the bocashi with application of microorganisms from capture one with a dose of 0.50 L/m3 became the best treatment with a total of $ 0.72 of marginal utility compared to commercial treatment and witness without application. Keywords: Microorganisms, Bocashi, Endemic, Commercial, organic fertilizer, macro and micronutrients.